Peningkatan Produktivitas UMKM Kuliner dengan Pendekatan Sustainable Human Resource Management Berbasis Sustainability Employee Life Cycle: Peningkatan Produktivitas UMKM Kuliner dengan Pendekatan Sustainable Human Resource Management Berbasis Sustainability Employee Life Cycle - Indah Wahyu Utami; Muhammad Ridwan Andi Purnomo (Journal Science Innovation and Technology (SINTECH), 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a key pillar in supporting regional economic growth, but they often face serious challenges in managing human resources (HR) sustainably to maintain productivity stability. Difficulties in retaining quality HRM have caused culinary MSMEs in Surakarta City to frequently face challenges in employee turnover and retention due to a lack of incentives and limited training. Culinary MSMEs have not been fully able to implement sustainable human resource practices. Many culinary MSMEs still face limitations in the use of environmentally friendly raw materials, waste management, and energy efficiency. The dilemma between needs and profitability causes additional costs. This study examines the application of Sustainable Human Resource Management (SHRM) with a Sustainability Employee Life Cycle (SELC) approach in increasing the productivity of Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector in Surakarta City. Using a mixed methods design, specifically Structural Equation Modeling (SEM) and Data Envelopment Analysis (DEA), on a sample of 60 culinary SME actors in Surakarta City. This study assesses the relationship between green recruitment practices, continuous training, value-based performance evaluation, and retention strategies on operational efficiency and human resource performance. The main dimensions analyzed in this model include green recruitment practices, continuous training, value-based evaluation, and employee retention strategies. The results show that the implementation of SHRM integrated with SELC can improve the performance of culinary MSMEs in line with the targets of each factor that supports sustainable productivity.